Urinary tract infection due to Staphylococcus lugdunensis in a 70-year-old woman with cystocele grade 3. Issue 4 (August 2015) - Munoz-Davila, M. J.; Perez, T.; Cascales, E.; Gallego, M. C.
Abstract : Introduction: Staphylococcus lugdunensis is a coagulase-negative staphylococci that is increasingly being reported as a human pathogen. Case presentation: Here, we describe a clinical case of urinary tract infection (UTI) due to S. lugdunensis in a 70-year-old woman with cystocele grade 3 who was successfully treated with cotrimoxazole. Although S. lugdunensis has rarely been reported to cause urinary tract infections and especially in immunosuppressed patients, we describe a case of UTI caused in an adult without the presence of an indwelling catheter or immunosuppression. Conclusion: S. lugdunensis can be a urinary tract pathogen in adults without the presence of indwelling catheters or other obvious medical problems. Urine cultures that show S. lugdunensis should not be attributed to skin contamination, especially when the clinical findings are compatible with cystitis or pyelonephritis.